Formulation of Liquid Hand Soap Made From Neem Seed Oil and Lemongrass Essential Oil - Fina Uzwatania; Riska Surya Ningrum; Sri Resti O (Indonesian Journal of Applied Research (IJAR), 2020)
The COVID-19 outbreak has overly emphasised the importance of handwashing with soap to reduce the spread of the virus. This study was conducted to formulate a liquid hand soap with neem oil and lemongrass essential oil as an natural antibacterial component. Three different concentrations of neem oil 5%; 10% and 15% and three different concentration of lemongrass essential oil (0.2%; 0.4%;0.6%) were formulated as liquid soap using coconut oil, castor oil and neem oil as its soap bases. The natural liquid soap was made by saponification reaction between oils and potassium hydroxide. The soap was evaluated for its pH value, density, foam stability, insoluble in alcohol content, free fatty acid and antibacterial activity. The results showed that the colour of the liquid soap was transparent with yellowish colored and had distinctive smell of neem oil. The pH values of the different formulated liquid hand soaps are within the accepted pH range of 4 - 10. The specific gravity was 1,083 – 1,088 g/ml. The foam stability range was 25.35% - 78.38%, respectively. The insoluble in alcohol content range were 0.14 – 0.4. The free caustic alkali range was 0.12 – 0.47. The liquid hand soap can inhibit the growth of Staphylococcus aureus. The inhibition zone diameter of liquid hand soap was 1.98- 2.61 cm. It was therefore proven that neem oil and lemongrass essensial oil is effective as an antibacterial component in the formulation of liquid hand soap.